Pollen morphology of Kalmia L. (Phyllodoceae, Ericaceae) and its taxonomic significance (Bangladesh Journal of Plant Taxonomy, 2012)
Pollen morphology of seven taxa of Kalmia was examined using light and scanning electron microscopy (LM and SEM, respectively), or SEM alone, in search of new characters that might contribute to infrageneric classification of the genus. The Kalmia species are stenopalynous and characterized by 3-colpor(oid)ate, medium, oblate pollen united in tetrahedral tetrads with rugulate exine sculpture. However, a continuous and serial variation in all the quantitative characters and exine sculpture was revealed within the genus. Kalmia buxifolia is characterized by having the smallest pollen tetrads, largest aperture, largest 2f/D ratio and septum thicker than apocolpial exine. On the other hand, K. latifolia produces the largest pollen tetrads with smallest aperture and smallest 2f/D ratio. An evolutionary trend from rugulate to psilate has also been observed in apocolpial exine sculpture of the genus Kalmia. On the basis of acetolysed pollen characteristics, a dichotomous key for Kalmia was prepared. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13126 Bangladesh J. Plant Taxon. 19(2): 123-133, 2012 (December)